2013
DOI: 10.1038/bjc.2013.127
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1/BRCA1 expression and gene polymorphisms as prognostic and predictive factors in advanced NSCLC treated with or without cisplatin

Abstract: Background:The FAST was a factorial trial in first-line treatment of advanced non-small-cell lung cancer (NSCLC), addressing the role of replacing cisplatin with a non-platinum agent. The prognostic and predictive effect of ERCC1/BRCA1 expression and ERCC1/XPD/XRCC1–3 gene polymorphisms on outcomes of patients was examined.Methods:Patients were randomised to receive treatment with or without cisplatin. ERCC1/BRCA1 expression was determined by immunohistochemistry. ERCC1 (C8092A, C118T), XPD (Lys751Gln), XRCC1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 44 publications
0
49
2
1
Order By: Relevance
“…Recently, accumulated preclinical and clinical studies have demonstrated that ERCC1 could be as a prognostic factor (information on the patients overall cancer outcome, regardless of therapy), predictive (information on the effect of a therapeutic intervention) and a potential therapeutic target in cancer, including NSCLC (13,17). In these studies, among patients who did not receive chemotherapy, those with ERCC1-positive tumors had longer survival than those with ERCC1-negative tumors (18), however, for the patients with ERCC1-negative tumors, they had a distinctly higher response rate (19) and attained benefit from platinum-based chemotherapy with significantly prolonged survival, but patients with ERCC1-positive tumors did not (18,20,21). In some other studies, inconsistently, ERCC1 expression was not associated with platinum response (22) or survival (23) in NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, accumulated preclinical and clinical studies have demonstrated that ERCC1 could be as a prognostic factor (information on the patients overall cancer outcome, regardless of therapy), predictive (information on the effect of a therapeutic intervention) and a potential therapeutic target in cancer, including NSCLC (13,17). In these studies, among patients who did not receive chemotherapy, those with ERCC1-positive tumors had longer survival than those with ERCC1-negative tumors (18), however, for the patients with ERCC1-negative tumors, they had a distinctly higher response rate (19) and attained benefit from platinum-based chemotherapy with significantly prolonged survival, but patients with ERCC1-positive tumors did not (18,20,21). In some other studies, inconsistently, ERCC1 expression was not associated with platinum response (22) or survival (23) in NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in ERCC1 genes are reported to be a potential predictor for the response to chemotherapy and clinical outcome of cancer patients, such nasopharyngeal carcinoma, colorectal cancer, and non-small cell lung as well as ovarian cancer (Chen et al, 2013;Moxley et al, 2013;Oguri et al, 2013;Tiseo et al, 2013). For gastric cancer, 2 systemic reviews indicated that ERCC1 rs11615C>T polymorphisms are useful prognostic factors in gastric cancer treated with platinum-based chemotherapy (Liu et al, 2011;Wang et al, 2012 Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Tubulin dimers consisting of TUBB3 compose microtubule polymers that interfere with the reaction to paclitaxel by slowing or blocking the transition from metaphase to anaphase in the mitotic cell cycle (15,16). Overall, these capable biomarkers have been demonstrated as prognostic and predictive markers in certain studies, but not in others (17)(18)(19)(20). Accordingly, the present prospective, randomized, non-interventional study was performed to verify the predictive value of the protein expression of ERCC1, BRCA1, RRM1 and TUBB3 in patients with NSCLC that received adjuvant cisplatin-based chemotherapy at the Sun Yat-Sen University Cancer Center (Guangzhou, Guangdong, China).…”
Section: Introductionmentioning
confidence: 99%